Ruxolitinib, IV Immunoglobulin, and High-Dose Glucocorticoids for Critically Ill Adults With Secondary Hemophagocytic Lymphohistiocytosis: A Single-Center Observational Pilot Study - Laura Scholz, MD; Florian Posch, MD, PhD; Eduard Schulz, MD, PhD; Max Gornicec, MD; Albert Wölfler, MD; Alexander C. Reisinger, MD, PhD; Andreas Reinisch, MD, PhD; Philipp Eller, MD; Florian Eisner, MD; Philipp Kreuzer, MD; Martin Stradner, MD; Alexander R. Rosenkranz, MD; et al. (Critical Care Explorations, 2024)
OBJECTIVES:. Secondary hemophagocytic lymphohistiocytosis (sHLH) is a cytokine-driven inflammatory syndrome that is associated with substantial morbidity and mortality and frequently leads to ICU admission. Overall survival in adults with sHLH remains poor, especially in those requiring intensive care. Classical chemotherapeutic treatment exhibits myelosuppression and toxicity. Recently, inhibition of Janus kinase signaling by ruxolitinib has shown efficacy in pediatric HLH. We therefore aimed to determine the activity and safety of a ruxolitinib-based regimen, in critically ill adults with sHLH. DESIGN:. Observational pilot study. SETTING:. Single-center tertiary academic ICU. PATIENTS:. Nine adults (≥ 18 yr) who fulfilled at least five of the eight HLH-2004 criteria. INTERVENTION:. Triplet regimen combining: 1) ruxolitinib, 2) polyvalent human IV immunoglobulins (IVIG) at a dose of 1 g/kg bodyweight for 5 days, and 3) high-dose corticosteroids (CSs, dexamethasone 10 mg/m² body surface area, or methylprednisolone equivalent) with subsequent tapering according to the HLH-2004 protocol. MEASUREMENT AND MAIN RESULTS:. Nine patients (median age: 42 yr [25th-75th percentile: 32–54]; male: n = 6 males, median H-score: 299 [255–304]) were treated with the triplet regimen. The median Sequential Organ Failure Assessment score at HLH diagnosis was 9 (median; 25th–75th percentile: 7–12), indicating multiple-organ dysfunction in all patients. Within 10 days a significant decrease of the inflammatory parameters soluble interleukin-2 receptor and ferritin as well as a stabilization of the blood count could be shown. All patients were alive at ICU discharge (100% ICU survival), 1 patient died after ICU discharge because of traumatic intracerebral hemorrhage that might be related to HLH or treatment, corresponding to an overall survival of 86% in a 6 months follow-up period. CONCLUSION:. In this small case series, a triplet regimen of ruxolitinib in combination with IVIG and CS was highly effective and save for treating critically ill adults with sHLH.